Civil Law Analysis of Life Insurance Agreements in the Context of Contractual Justice for Consumer - Ardelina Ayu Lestari; Dini Sakinah; Bahzi Atsil; Nurul Fattah Poham; Ibnu Farhan (ISNU Sumatera Utara, 2025)
A life insurance contract is a form of contractual agreement between an insurance company as a business actor and the insured as a consumer. In practice, the imbalance in position between the two parties often gives rise to issues of contractual fairness, particularly when the policy terms and conditions tend to be unilateral and not fully understood by the consumer. This study aims to analyze life insurance contracts based on the principles of civil law, particularly the principles of freedom of contract, good faith, and balance in the contract. The research method used is a normative juridical approach with a literature review of laws and regulations, legal doctrine, and relevant court decisions. The results of the analysis indicate that although formally the life insurance contract meets the requirements for a valid contract according to Article 1320 of the Civil Code, the substance of the contract clauses often contradicts the principle of fairness, particularly in terms of exclusions of coverage, unilateral cancellation, and premium provisions. Therefore, it is necessary to enforce the principle of consumer protection through strict supervision by relevant authorities such as the Financial Services Authority (OJK), as well as legal interpretation that favors substantial justice for consumers. This study concludes that updating the contract model and strengthening regulations are necessary to ensure a balance of rights and obligations between parties in a life insurance agreement.